2014
DOI: 10.1371/journal.ppat.1003875
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Vaccination Promotes Detrimental Th17-Mediated Immunity against Influenza Infection

Abstract: Influenza disease is a global health issue that causes significant morbidity and mortality through seasonal epidemics. Currently, inactivated influenza virus vaccines given intramuscularly or live attenuated influenza virus vaccines administered intranasally are the only approved options for vaccination against influenza virus in humans. We evaluated the efficacy of a synthetic toll-like receptor 4 agonist CRX-601 as an adjuvant for enhancing vaccine-induced protection against influenza infection. Intranasal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 34 publications
2
78
1
Order By: Relevance
“…PLGA MS themselves also help to circumvent toler ance as they are specifically taken up by professional antigen presenting cells. A study by Maroof et al showed, that intranasal vaccination with a TLR4 agonist and a detergent split influenza antigen promotes antigen specific antibody responses but also polyfunctional antigen specific Th17 cells leading to increased weight loss and morbidity during the early stages of disease [43]. The utilization of CpG ODN and polyI:C in our vaccination protocol, in contrast, generates a strong Th1 polarizing condition, which in combination with the usage of a peptide exclusively presented on HLA A*0201 to CD8 + cytotoxic T cells, limits the danger of the induction of an unwanted Th17 cell mediated, vaccine induced IL 17 response.…”
Section: Discussionmentioning
confidence: 99%
“…PLGA MS themselves also help to circumvent toler ance as they are specifically taken up by professional antigen presenting cells. A study by Maroof et al showed, that intranasal vaccination with a TLR4 agonist and a detergent split influenza antigen promotes antigen specific antibody responses but also polyfunctional antigen specific Th17 cells leading to increased weight loss and morbidity during the early stages of disease [43]. The utilization of CpG ODN and polyI:C in our vaccination protocol, in contrast, generates a strong Th1 polarizing condition, which in combination with the usage of a peptide exclusively presented on HLA A*0201 to CD8 + cytotoxic T cells, limits the danger of the induction of an unwanted Th17 cell mediated, vaccine induced IL 17 response.…”
Section: Discussionmentioning
confidence: 99%
“…Mice immunized with an influenza vaccine adjuvanted with a synthetic TLR-4 agonist via the nasal route, exhibited a transient, enhanced IL-17A pathology, characterized by weight loss and morbidity, which was significantly greater than observed in mice given no-adjuvanted antigen. 41 The effect of adjuvants on induction of tolerance has also been noted; an intranasal co-administration of hen egg lysozyme with a TLR2 ligand enhanced Th1-type antibodies in one case, 118 while another TLG2 ligand, Pam3Cys, was shown to increase the risk of developing autoimmune disease 119 PLGA nanoparticles have been shown to boost tolerance in suppression of arthritis 120 and further research by the same group has shown that they are responsible for generation of enhanced Treg cell induction. 68 …”
Section: Adjuvantsmentioning
confidence: 99%
“…40 Later research has indicated that the response is more nuanced, with some contradictory evidence regarding advantages and disadvantages of IL-17A induction. 41,42,43 Predominance of one set of cytokines over the other is generally indicative of polarization of Th responses, for example the presence of IL-4 and absence of IFN-g indicate a classical Th-2 polarized immune reaction 44 although these cytokines can also be released at the same time. 45,46,47 The varying cytokine profiles related to CTL and antibody production are fundamental in affording protection against a specific pathogen.…”
Section: Respiratory Epithelial Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Less is known about the role of Th17 cells during respiratory infections. They are important effector cells at mucosal sites, including the lung, and are detected in severe influenza virus infections, suggesting a role in tissue pathology (11,14,19,27). Another subset of effector CD4…”
Section: T Cells and May Involve Developmentally Induced Changes In Smentioning
confidence: 99%